2021
DOI: 10.1093/nar/gkab1080
|View full text |Cite
|
Sign up to set email alerts
|

dbAMP 2.0: updated resource for antimicrobial peptides with an enhanced scanning method for genomic and proteomic data

Abstract: The last 18 months, or more, have seen a profound shift in our global experience, with many of us navigating a once-in-100-year pandemic. To date, COVID-19 remains a life-threatening pandemic with little to no targeted therapeutic recourse. The discovery of novel antiviral agents, such as vaccines and drugs, can provide therapeutic solutions to save human beings from severe infections; however, there is no specifically effective antiviral treatment confirmed for now. Thus, great attention has been paid to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(54 citation statements)
references
References 64 publications
0
54
0
Order By: Relevance
“…Research studies showed that DP7, an AMP designed in silico, showed broad-spectrum antimicrobial activity against MDR bacteria, such as P. aeruginosa [102]. Currently, there are many antimicrobial peptides databases (APDs) such as APD3 [63] and collection of antimicrobial peptides (CAMP)R3 [103], as well as online tools for AMP screening and identification such as dbAMP [104] and Ensemble-AMPPred [105].…”
Section: In Silico Designmentioning
confidence: 99%
“…Research studies showed that DP7, an AMP designed in silico, showed broad-spectrum antimicrobial activity against MDR bacteria, such as P. aeruginosa [102]. Currently, there are many antimicrobial peptides databases (APDs) such as APD3 [63] and collection of antimicrobial peptides (CAMP)R3 [103], as well as online tools for AMP screening and identification such as dbAMP [104] and Ensemble-AMPPred [105].…”
Section: In Silico Designmentioning
confidence: 99%
“…Drug toxicity remains a latent issue [ 20 ], and peptides are no exception to this rule [ 21 ]. Although databases reveal more than 10,000 unique bioactive peptide sequences [ 22 , 23 ], less than 1% of this group became FDA-approved drugs. Several bioactive peptides have shown toxicity, especially their disruptive action on red blood cells (RBCs) [ 24 ].…”
Section: Peptide Drugs Market and Discovery: A Bird’s Eye Viewmentioning
confidence: 99%
“…To date, the structures of 26,447 AMPs are known and 3444 of them are molecularly characterized with defined tertiary structure ( Figure 1 ) [ 27 ].…”
Section: Introductionmentioning
confidence: 99%